An Investigation on Reading Flow Experience Among EFL Indonesian Students - Siregar, Fenty Lidya; Henni, Henni (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2024)
Abstract. This study investigated students’ perception of flow experience (FE) when reading extensively and conditions that enabled FE. The participants were 36 EFL students from a private university in West Java, Indonesia who were involved in an extensive reading (ER) program using the XReading application. This study is a quantitative study which data were collected through questionnaire distribution and students’ reading results in Xreading. Regarding the findings, it was found that the students experienced flow during their extensive reading. Specifically,  although when joining ER for two semesters the students experienced flow, the flow experience in the two semesters is high. Second, the study found that the most significant condition for the students to experience flow is feedback. Third, the correlation result between students’ flow and the numbers of words they read in the first and second semester were respectively not statistically significant and technically a positive correlation. However, the relationship between the variables is weak in the second semester, The result also showed that in the 2nd semester the larger the number of words read, the higher the students’ flow experience is which indicated that more often the students do ER, the bigger their chance to experience flow.  Therefore, increasing students’ opportunities for experiencing flows could improve the quality of their language learning.Keywords: Flow, Extensive Reading, Optimal Experience